2018
DOI: 10.2478/ijame-2018-0042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Variable Viscosity on MHD Inclined Arterial Blood Flow with Chemical Reaction

Abstract: In this paper, we present the mathematical study of heat and mass transfer effects on an arterial blood flow under the influence of an applied magnetic field with chemical reaction. A case of mild stenosis is considered in a non-tapered artery which is inclined at an angle γ from the axis. The variable viscosity of the blood is considered varying with the hematocrit ratio. Governing non-linear differential equations have been solved by using an analytical scheme, homotopy perturbation method to obtain the solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…Figure 3 reveals through parabolic axial velocity profile that axial velocity has its maximum value at the centerline of the artery and a slip at wall fairly enhances? The blood flow velocity as compared to no-slip condition for different values of the slip parameter h , which is in agreement with the studies carried out by in the works [20,22,27,30]. Figure 4 demonstrates the influence of amplitude of the body acceleration G 0 on axial velocity in the stenosed section and it is observed that by increasing slowly the value of the parameter G 0 , we can increase fluid velocity but higher values show the reverse behaviour.…”
Section: Graphical Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Figure 3 reveals through parabolic axial velocity profile that axial velocity has its maximum value at the centerline of the artery and a slip at wall fairly enhances? The blood flow velocity as compared to no-slip condition for different values of the slip parameter h , which is in agreement with the studies carried out by in the works [20,22,27,30]. Figure 4 demonstrates the influence of amplitude of the body acceleration G 0 on axial velocity in the stenosed section and it is observed that by increasing slowly the value of the parameter G 0 , we can increase fluid velocity but higher values show the reverse behaviour.…”
Section: Graphical Results and Discussionsupporting
confidence: 91%
“…Sankad and Nagathan [29] discussed the transport of an MHD couple stress fluid through peristalsis in a porous medium under the influence of the heat transfer and slip effects. Tripathi and Sharma [30] focused on the study of effects of heat and mass transfer on an arterial blood (with variable viscosity) flow in the presence of the applied magnetic field with chemical reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies [6][7][8][9] investigated the influence of variable viscosity, when the viscosity is dependent on the distance only. However, some researches considered the influence of the viscosity when it is dependent on the temperature [10][11][12]. Also, It was established that the influences of heat and mass transfer hold significant roles in peristaltic flow, as in blood flux processes, kidney dialysis and cancer medicament.…”
Section: Issn: 0067-2904mentioning
confidence: 99%
“…Figures- (11)(12)(13)(14)(15)(16) are plotted to illustrate the effects of different parameters on the concentration profile. In Figures-(11-13), it is noticed that the concentration profile decreases with the increase in Schmidt number ( ), Soret number ( ) and the heat source / sink parameter ( ).…”
Section: 3-concentration Profilementioning
confidence: 99%
“…Latha and Kumar [11] did a research that studied MHD unsteady flow of blood through a medium that is porous in a plate channel that is parallel and Vincent et al [12] did a study of velocity profile for unsteady blood flow through a tube that is circular and inclined in the presence of a magnetic field. Tripathy and Sharma [13] did a research that studied the effect of variable viscosity on MHD inclined arterial flow of blood with chemical reaction present while Islam Eldesoky [14] did a mathematical analysis of MHD flow of blood that is unsteady through a channel plate that is parallel with heat source present. His research showed shows that when there is an increase in the heat source, the axial velocity and the temperature will increase while the normal velocity and Prandtl number decreases with an increase in the decay parameter.…”
Section: Introductionmentioning
confidence: 99%